From gradual erosion to revitalization: National Social Dialogue Institutions and policy effectiveness. (March 2022) - Guardiancich, Igor; Molina, Oscar
We explore the factors behind the long-term erosion of National Social Dialogue Institutions (NSDIs) to provide insights about the conditions for their revitalization. By applying policy analysis insights into the industrial relations field, we argue that limited policy effectiveness goes a long way towards explaining the erosion experienced by many NSDIs worldwide in recent years. Drawing on a global survey and on case studies of NSDIs in Brazil, Italy and South Korea, we show that these institutions' policy effectiveness crucially depends on combinations of their problem-solving capacity, an encompassing mandate to deal with relevant socioeconomic issues and an enabling environment that grants the inclusion of social dialogue into decision making. With regard to rekindling their role, the article provides substantial evidence that two sub-dimensions of effectiveness are key: enjoying political support and having an 'effective mandate' as opposed to relying on just a formal remit to deal with socioeconomic issues of interest.